Climate and hydric deficit in the steppe ecosystem of Lécera, Spain - Blasco, Mario (Revista de Ciencias Agrícolas, 2013)
The Lécera (41º12´ Lat N, 0º 43´ Long E, 530 m altitude) land is a representative part of the steppe (about 10,000 km.2) covering the central area of the river Ebro Valley, Zaragoza, Spain. The Lécera steppe is located over Tertiary Miocenic sediment (calcic/gypsic). The average climate data/year are:13,4 ºC,+ 395.8 mm-1 m-2 rainfall, and 53,6% relative humidity,5.22 m-1sg-1 wind speed, extraterrestrial radiation and solar radiation amounted 836 and 352,8 MJ m-2 monthly respectively, insolation average was 158,6 h-1 /month. According to those data, the climate is semiarid, temperate with mediterranean (Mediterranean Sea) influence. It can be said that cierzo, the dry and strong wind that sweeps the whole steppe, has a very important desiccation impact. Rso and FAO, Penman, Monteith equation were used to determine, respectively, evaporation and evapotranspiration. Neat potential evaporation comes up to 1,401.2 mm-1 m-2.per year, and neat potential evapotranspiration amounted to 1,508,8 mm-1m-2 year, causing a very high hydric stress.